PENETAPAN KADAR ETANOL PADA TAPE SINGKONG (Manihot utilissima) DENGAN PENAMBAHAN SARI BUAH NANAS (Ananas comosus) - Siti Nurbaya; Siti Maimunah; Zuhairiah Zuhairiah; Ika Kristina (Jurnal Farmanesia, 2019)
Cassava tape is a tape made from fermented cassava. The fermentation process is one way to turn food into the product we want by using microbes. This study aims to determine the effect of adding pineapple juice (Ananas comosus) to the ethanol content of cassava tape (Manihot utilissima). Experimental research method with distillate examination, in the distillation process. The sample used was cassava tape (Manihot utilissima) with variations in the volume of addition of pineapple juice (Ananas comosus) 50 ml, 60 ml, and 70 ml, with a fermentation time of 3 days. The sampling technique used is purposive sampling. The results of weighing the ethanol content with a pycnometer will be matched based on its specific gravity. The results of the study of ethanol levels in cassava tape (Manihot utilissima) with a volume variation of the addition of 50 ml of pineapple juice (Ananas comosus) obtained 2.71% results, with the addition of 60 ml the results were 3.19%, with the addition of 70 ml the results were 3.88%. Meanwhile, the ethanol content of cassava tape (Manihot utilissima) without pineapple juice (Ananas comosus) was found to be 1.88%. The conclusion of this study was that the ethanol content of cassava tape (Manihot utilissima) with the addition of pineapple juice (Ananas comosus) increased.